Confined blood chimerism in a monochorionic dizygotic sex discordant twin pregnancy conceived after induced ovulation. Issue 4 (2nd March 2016) - Mayeur Le Bras, Anne; Petit, François; Benachi, Alexandra; Bedel, Bettina; Oucherif, Salima; Martinovic, Jelena; Armanet, Narjes; Tosca, Lucie; Gautier, Valérie; Parisot, Frédéric; Labrune, Philippe; Tachdjian, Gérard; et al.
Abstract : Background: Monochorionic twins are generally considered as a monozygotic twin pregnancy. However, several cases of monochorial dizygotic twin pregnancies have been reported. Case Report: We report on a rare case of monochorionic dizygotic twin pregnancy conceived after induced ovulation in a 32‐year‐old woman. The diagnosis was made on morphological ultrasound examination at 18+4 weeks of gestation, showing two fetuses with discordant sex. The amniocentesis was declined by the patient. Results: The monochorionic status was confirmed after a histopathalogical study of the placenta. At delivery, both a phenotypically normal boy and a phenotypically normal girl without sexual abnormality were observed. This analysis also revealed the presence of vascular anastomoses between both fetal circulations. Postnatal cytogenetic analyses indicated the presence of a chimerism in peripheral blood lymphocytes. This chimerism was not observed in cells obtained from a buccal swab. Molecular determination of zygosity confirmed the existence of the confined peripheral blood chimerism with the presence of four parental alleles. Conclusion: We report on a case of monochorionic dizygotic twin pregnancy. This observation underlies the need to carefully assess twin pregnancies, especially when obtained after assisted reproductive technology. Birth Defects Research (Part A) 106:298–303, 2016. © 2016 Wiley Periodicals, Inc.